2023
DOI: 10.3389/fnetp.2023.1276899
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory dynamics during respiratory maneuver in athletes

Oleksandr Romanchuk

Abstract: Introduction: The modern practice of sports medicine and medical rehabilitation requires the search for subtle criteria for the development of conditions and recovery of the body after diseases, which would have a prognostic value for the prevention of negative effects of training and rehabilitation tools, and also testify to the development and course of mechanisms for counteracting pathogenetic processes in the body. The purpose of this study was to determine the informative directions of the cardiorespirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 167 publications
(163 reference statements)
0
5
0
1
Order By: Relevance
“…However, in our opinion, it is not able to adequately reflect changes both at rest and during exercise, since this coefficient does not take into account the volumetric characteristics of the cardiorespiratory system, which determine its energy capabilities both at rest and under exercise time It was previously shown that IH (cu) in a group of physically active men when performing tests with controlled breathing likely increases from 4. 77 (3.98; 6.20) to 10.92 (9.97; 12.14), p=0.000 at CR 6 and remains unchanged in comparison with spontaneous breathing 5.00 (4.48, 5.84), p=0.209 at CR 15 (Romanchuk, 2023). Other authors demonstrated its increase during physical load, which occurred due to a relative increase in heart rate (min -1 ) compared to HR (min -1 ).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…However, in our opinion, it is not able to adequately reflect changes both at rest and during exercise, since this coefficient does not take into account the volumetric characteristics of the cardiorespiratory system, which determine its energy capabilities both at rest and under exercise time It was previously shown that IH (cu) in a group of physically active men when performing tests with controlled breathing likely increases from 4. 77 (3.98; 6.20) to 10.92 (9.97; 12.14), p=0.000 at CR 6 and remains unchanged in comparison with spontaneous breathing 5.00 (4.48, 5.84), p=0.209 at CR 15 (Romanchuk, 2023). Other authors demonstrated its increase during physical load, which occurred due to a relative increase in heart rate (min -1 ) compared to HR (min -1 ).…”
Section: Discussionmentioning
confidence: 89%
“…When studying VSI (dm 3 ×L -1 ), which characterizes volumetric synchronization, it was previously shown that when performing a breathing maneuver with a change in respiratory rate, it reliably decreases from 0.586 (0.477; 0.745) in SR to 0.441 (0.327; 0.582) at CR 6 to 0.360 (0.247; 0.477), p=0.000 at CR 15 (Romanchuk, 2023). In other studies, it was found that it increases with work capacity (Gastinger, et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations